EFEKTIVITAS PENDEKATAN SUPERVISI PENGAJARAN NON-DIREKTIF PENGAWAS AGAMA HINDU - Ida Bagus Nyoman Rai Wiyadnyana (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2016)
The implementation of the non-directive learning supervision is very representative in enhancing the ability of the teachers of Hinduism to serve PAIKEM learning within the elementary schools that belong to the Klusa group in the district of Payangan, Gianyar, due to: First, there is also an increase of the teachers’ competence in developing the learning scenarios. Second, the percentage of teachers’ ability in presenting the PAIKEM learning is also increasing significantly by 84% which is in the pre-cycle only reaches 16% or only 1 teacher is considered in the good category. On the first cycle it is of 66% that means there are 4 teachers who are in the goodcategory and on the the second cycle the percentage reaches 100% or all the teachers, the research subjects, has been able to complete the PAIKEM learning.Thus, this study has been finished on the second cycle because conceptually the research indicators have been achieved. In general, the implementation levels of the non-directive learning supervision have already been performed according to the plan.